Examining the Role of Sphingosine Kinase‐2 in the Regulation of Endothelial Cell Barrier Integrity. (April 2016) - Dimasi, David P.; Pitson, Stuart M.; Bonder, Claudine S.
Abstract: Objective: A key mediator of vascular EC barrier integrity, S1P, is derived from phosphorylation of sphingosine by the SK‐1 and SK‐2. While previous work indicates that SK‐1 can regulate EC barrier integrity, whether SK‐2 has a similar role remains to be determined. Methods: A cell impedance assay was used to assess human umbilical vein EC and bone marrow EC barrier integrity in vitro, with application of the SK inhibitors ABC294640, PF543, SKi, and MP‐A08. In vivo studies were conducted using intravital microscopy to assess EC barrier integrity in SK‐1 ( Sphk1 −/− ) and SK‐2 ( Sphk2 −/− ) knock‐out mice. Results: Only ABC294640 and MP‐A08, which can both inhibit SK‐2, caused a decrease in EC barrier integrity in vitro in both cell types. Intravital microscopy revealed that Sphk1 −/− mice had reduced EC barrier integrity compared to WT mice, whereas no change was evident in Sphk2 −/− mice. Conclusions: Our data suggest that in vitro inhibition of SK‐2, can compromise the integrity of the EC monolayer, while SK‐1 exerts a more dominant control in vivo . These data may have clinical implications and could aid in the development of new treatments for disorders of vascular barrier function.